Sistematización de la experiencia de medición de Clima Laboral y propuesta del Plan de Mejora en el Instituto Nacional de Donación y Trasplante de Órganos, Tejidos y Células-INDOT, en la ciudad de Quito el período enero a julio 2017. - Bravo Gaona, Byron Geovanny (2017)
This report exposes the systematization of the experience of measuring the labor climate of the Instituto Nacional de Donación y Transplante de Organos, Tejidos y Celulas, INDOT, as well as the plan for improvement in the city of Quito during the period between January and July of 2017. The completion of such was possible by using the theoretical bases of cognitive standard of psychology while realizing a mixed focus field study. The basis of the project assumes that the development of a healthy workplace environment depends of organizational and personal factors that contribute to an environment that is relevant in the achievement of the strategic objectives of the organization as well as the wellbeing of it’s members. The use of a questionnaire about the work place climate helped in the identification of the perception of servers in relationship to the prevailing environment of the institution. The implementation of an analytical / descriptive process to the statistical information aided in identifying that the workplace environment or climate were favorable albeit with aspects that could be strengthened in relation to; autonomy and confidence, communication, leadership, innovation and team synergy. An action plan was proposed in order to establish a positive perspective on the workplace environment of the institution.